Mechanical vibrations - Den Hartog, J. P. (Dover Publications, 1985)
This book aim to be as simple as is compatible with a reasonably complete treatment of the subject. They are electronic measuring instruments and the theory and practice of instrumentation, servomechanisms and control or systems engineeing,...